Kazakhstani native cattle reveal highly divergent mtDNA from Bos taurus and Bos indicus lineages with an absence of Bos indicus Y chromosome. (25th October 2018) - Yamanaka, Hayate; Murata, Kako; Tabata, Risa; Kawaguchi, Fuki; Sasazaki, Shinji; Yamamoto, Yoshio; Bakhtin, Meirat; Kazymbet, Polat; Meldevekob, Alykhan; Suleimenov, Maratbek Z.; Nishibori, Masahide; Mannen, Hideyuki
Abstract: Kazakhstan is the largest landlocked country and contains two important propagation routes for livestock from the Fertile Crescent to Asia. Therefore, genetic information about Kazakhstani cattle can be important for understanding the propagation history and the genetic admixture in Central Asian cattle. In the present study, we analyzed the complete mtDNA D‐loop sequence and SRY gene polymorphism in 122 Kazakhstani native cattle. The D‐loop sequences revealed 79 mitochondrial haplotypes, with the major haplogroups T and I. The Bos taurus subhaplogroups consisted of T (3.3%), T1 (2.5%), T2 (2.5%), and T4 (0.8%) in addition to the predominant subhaplogroup T3 (86.9%), and the Bos indicus subhaplogroup of I1 (4.1%). Subsequently, we investigated the paternal lineages of Bos taurus and Bos indicus, however, all Kazakhstani cattle were shown to have Y chromosome of Bos taurus origin. While highly divergent mtDNA subhaplogroups in Kazakhstani cattle could be due to the geographical proximity of Kazakhstan with the domestication center of the Fertile Crescent, the absence of Bos indicus Y chromosomes could be explained by a decoupling of the introgression dynamics of maternal and paternal lineages. This genetic information would contribute to understanding the genetic diversity and propagation history of cattle in Central Asia.